2021
DOI: 10.1111/jcmm.16961
|View full text |Cite
|
Sign up to set email alerts
|

m6A regulator‐mediated RNA methylation modification patterns and immune microenvironment infiltration characterization in severe asthma

Abstract: Asthma is a chronic airway inflammatory disease with obvious heterogeneity and complex pathophysiological manifestations. 1 At present, there are at least 300 million cases of asthma in the world, and the prevalence of asthma is increasing year by year. 2 Severe asthma refers to the severe state of asthma. Although severe asthma accounts for a small proportion of the total number of asthma, its direct medical costs account for 50% of the total cost of asthma treatment. 3 Severe asthma is difficult to control,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…These studies suggest that the expression changes of key genes related to m6A regulators function may lead to phenotypic alteration. In addition, our previous research has shown that m6A regulator–mediated RNA methylation modification was involved in asthma ( Sun et al, 2021 ). In this study, we will continue to investigate the relationship between m6A and asthma; we systematically evaluated the transcriptome-wide m6A methylome and m6A-modified genes in asthma by methylated RNA immunoprecipitation sequencing (MeRIP-seq) and RNA sequencing (RNA-seq).…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggest that the expression changes of key genes related to m6A regulators function may lead to phenotypic alteration. In addition, our previous research has shown that m6A regulator–mediated RNA methylation modification was involved in asthma ( Sun et al, 2021 ). In this study, we will continue to investigate the relationship between m6A and asthma; we systematically evaluated the transcriptome-wide m6A methylome and m6A-modified genes in asthma by methylated RNA immunoprecipitation sequencing (MeRIP-seq) and RNA sequencing (RNA-seq).…”
Section: Introductionmentioning
confidence: 99%
“…The role of YTHDF2 in preventing excessive inflammatory responses is a potential therapeutic target for inflammatory diseases ( Yu et al, 2019 ). One study classified severe asthma into three m6A modification patterns, which can achieve precise treatment according to the characteristics of the immune microenvironment ( Sun et al, 2021 ). Lynall et al (2020) stratified patients with depression according to their leukocyte subsets and found that the inflammatory depression subgroup had more severe depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested a fundamental role for m6A modifications in the tumor immune microenvironment ( Han et al, 2019 ; Zhang et al, 2020 ). More recent studies revealed that m6A plays a similarly crucial role in the immune microenvironment of periodontitis ( Zhang et al, 2021 ) and severe asthma ( Sun et al, 2021 ). For multifaceted diseases such as depression, which is influenced by multiple factors such as genetic susceptibility and the inflammatory response, early diagnosis and treatment are critical.…”
Section: Introductionmentioning
confidence: 99%
“…Many severe asthma patients show abnormal YTHDF3 and YTHDC1 expression. YTHDF3 is responsible for shifting the immune microenvironment, resulting in increased eosinophil infiltration (D. Sun et al, 2021). A frequent consequence of lung transplantation is lung ischemia‐reperfusion injury (LIRI).…”
Section: Role Of Yth Domain Family (Ythdf) Proteins In Human Physiolo...mentioning
confidence: 99%